Does gender and sexual diversity lead to greater conflict in the school? - Verónica Frisancho Robles; Alejandro Herrera; Eduardo Nakasone (Inter-American Development Bank (IDB), 2022)
Diversity in gender identity and sexual orientation challenges traditional institutions, social norms, and gendered stereotypes. This may translate into greater levels of conflict in s ociety. Using data from 95 middle and high schools in Uruguay, we exploit plausibly exogenous variation in the share of LGBT students across classrooms and estimate its impact on the prevalence of psychological, physical, and sexual violence in the school. On average, we do not find support for a strong link between the share of LGBT students in the classroom and the prevalence of violence, yet we show that there are gendered effects of greater diversity: a larger share of LGBT students in the classroom is associated with greater levels of psychological and physical violence among LGBT girls.
Keywords: J16; J24; I21; I24; 330; LGBT; Diversity; Conflict; Contact hypothesis; Violence; Secondaryschool